Establishment of Reference Intervals for Fasting and Non- fasting Serum Lipid Profile from Healthy Population - Jaswanth Kumar P; B Sheshu Kumar (International Journal of Health and Clinical Research, 2021)
Background: A lipid profile is a combination of blood tests performed to check the cholesterol levels and the level of triglycerides in the blood. High cholesterol is linked to heart diseases, obesity, diabetes, etc. Those who are at a higher risk of these conditions or have been diagnosed with these issues need to undergo a lipid profile. Various factors affect lipid profile parameters like age, ethnicity, diet, genetic and gender differences and this makes is essential to establish a reference range of the values of serum lipids for specific population in India. This study was done to evaluate the reference values of lipid profile of a sub urban South Indian population as per the guidelines of the National Cholesterol Education Program (NCEP) of the USA. Reference values used in most of the laboratory are based on the western population in most laboratories and they do not have any similarity with the Indian population, because of many variables and this applies more specifically in case of the lipid profile. These western studies based reference values are used by almost all clinicians worldwide, to interpret the results obtained in patients, it should correctly represent the defined population having close comparison with the patient coming for investigation. As very less documented evidence on establishment of reference levels for lipids parameters for the Indian population, so there is a need for large scale study on lipid profile of Indian population. Materials and methods: A cross-sectional study, including 200 subjects in total (according to CLSI guidelines) were analyzed in fasting and non fasting states for the same patient, for total cholesterol, triglycerides, HDL-cholesterol by standard methods and, LDL-cholesterol was calculated using Friedewald’s formula. Results: After analysis, Mean values and ranges(2.5–97.5th percentile) in mg/dL for fasting and nonfasting TC, TG, VLDL, LDL-C ,HDL-C were: 110-240 , 39.2 - 174.2, 57.2 - 172.0, 8.0 - 42.0, 32-72.0 in fasting and 116.2 - 252.2, 44.0 - 280.2, 52 - 180.2, 8.6 - 56.2, 26-68.0 in non fasting respectively . After grouping them according to age and sex, we observed that HDL-C was significantly wider in females compared to males, TC was not significantly wider, but TG was higher in males. In the age group 46- 55 years TC, TG, HDL-C and LDL-Cholesterol in males were higher as compared to females of that age group.Conclusion: Reference ranges are wider as compared to western standard, which is due to variation in diet, ethnicity, environment, etc. Hencethis can be considered as the reference interval for this study population, further study is needed in a larger population.